2002
DOI: 10.1074/jbc.m202101200
|View full text |Cite
|
Sign up to set email alerts
|

Direct Effects of Caffeine and Theophylline on p110δ and Other Phosphoinositide 3-Kinases

Abstract: We investigated the effects of methylxanthines on enzymatic activity of phosphoinositide 3-kinases (PI3Ks). We found that caffeine inhibits the in vitro lipid kinase of class I PI3Ks (IC 50 ‫؍‬ 75 M for p110␦, 400 M for p110␣ and p110␤, and 1 mM for p110␥), and theophylline has similar effects (IC 50 ‫؍‬ 75 M for p110␦, 300 M for p110␣, and 800 M for p110␤ and p110␥) and also inhibits the ␣ isoform of class II PI3K (PI3K-C2␣) (IC 50 Ϸ 400 M). However, four other xanthine derivatives tested (3-isobutyl-1-meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
98
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(106 citation statements)
references
References 44 publications
(53 reference statements)
7
98
0
1
Order By: Relevance
“…However, it has also been reported that caffeine has inhibitory effects on the phosphoinositide metabolism, including inhibition of the enzymatic activity of PI3K (12). Furthermore, caffeine and PTEN have been found to act synergistically regarding growth inhibition and the induction of apoptosis in cancer cells by the downregulation of the PI3K/Akt pathway (13), suggesting the antiproliferative effects of caffeine that are comparable with those of PTEN.…”
Section: Introductionmentioning
confidence: 89%
“…However, it has also been reported that caffeine has inhibitory effects on the phosphoinositide metabolism, including inhibition of the enzymatic activity of PI3K (12). Furthermore, caffeine and PTEN have been found to act synergistically regarding growth inhibition and the induction of apoptosis in cancer cells by the downregulation of the PI3K/Akt pathway (13), suggesting the antiproliferative effects of caffeine that are comparable with those of PTEN.…”
Section: Introductionmentioning
confidence: 89%
“…As a consequence of Akt activation, apoptosis in these tumor cells was suppressed. Conversely, caffeine-treated mice displayed decreased activation of the Akt pathway, most possibly due to the inhibitory effect of caffeine on kinase activity of PI3K (37). Activation of the Akt pathway can increase cell proliferation or/and inhibit apoptosis (38), which has been shown to provide cell survival signals essential to tumor formation induced by the PyMT antigen (39).…”
Section: Discussionmentioning
confidence: 99%
“…These additional pathways included the Akt pathway and its downstream target, the caspase-dependent apoptosis pathway (37). It was important to note that these pathways were not consistently regulated by caffeine exposure and genetic variation.…”
Section: Discussionmentioning
confidence: 99%
“…Theophylline (5 mM) strongly inhibits mTOR kinase activity in vitro and blocked insulin activation of Akt in 3T3-L1 adipocytes [73]. However, since theophylline and caffeine also target class I PI3Ks with IC 50 values ranging from 75 μM to 1 mM [74], effects on Akt cannot be attributed solely to mTOR inhibition. Caffeine has been used extensively in cell-based experiments to investigate cell cycle checkpoints in G1/S and G2/M that are induced by DNA damage.…”
Section: Mtor Kinase Inhibitorsmentioning
confidence: 99%
“…By contrast, mutations in the FRB that cause rapamycin resistance decrease TOR1 kinase activity, again highlighting the idea that this domain regulates TOR1 activity in multiple ways. Caffeine and theophylline also block the activity of class II PI3K C2α (IC 50~0 .4 mM) [74].…”
Section: Mtor Kinase Inhibitorsmentioning
confidence: 99%